The integration of genetically-regulated transcriptomics and electronic health records highlights a pattern of medical outcomes related to increased hepatic transthyretin expression. (3rd April 2022) - Pathak, Gita A.; De Lillo, Antonella; Wendt, Frank R.; De Angelis, Flavio; Koller, Dora; Cabrera Mendoza, Brenda; Jacoby, Daniel; Miller, Edward J.; Buxbaum, Joel N.; Polimanti, Renato
Abstract: Transthyretin (TTR) is the precursor of the fibrils that compromise organ function in hereditary and sporadic systemic amyloidoses (ATTR). RNA-interference and anti-sense therapeutics targeting TTR hepatic transcription have been shown to reduce TTR amyloid formation. In the present study, we leveraged genetic and phenotypic information from the UK Biobank and transcriptomic profiles from the Genotype-Tissue Expression project to test the association of genetically regulated TTR gene expression with 7149 traits assessed in 420, 531 individuals. We conducted a multi-tissue analysis of TTR transcription and identified an association with a operational procedure related to bone fracture ( p = 5.46×10 −6 ). Using tissue-specific TTR expression information, we demonstrated that the association is driven by the genetic regulation of TTR hepatic expression (odds ratio [OR] = 3.46, p = 9.51×10 −5 ). Using the UK Biobank electronic health records (EHRs), we investigated the comorbidities affecting individuals undergoing this surgical procedure. Excluding bone fracture EHRs, we identified a pattern of health outcomes previously associated with ATTR manifestations. These included osteoarthritis (OR = 3.18, p = 9.18×10 −8 ), carpal tunnel syndrome (OR = 2.15, p = .002), and a history of gastrointestinal diseases (OR = 2.01, p = 8.07×10 −4 ). In conclusion, our study supports that TTR hepatic expression can affect health outcomes linked to physiological and pathological processes presumably related to the encoded protein.